Festival as Ritual - Rituals in Festival: Symbolic Expressions in Modern Finnish Local Festivals - Salmi-Niklander, Kirsti (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1992)
A lively new tradition of modern local festivals began in Finland at the end of the 1960s and the beginning of the 1970s. This article is based on fieldwork carried out in 1983 on two local festivals. Both the ritualistic elements and the ritual meaning of these festivals as a whole are analyzed. First, the cultural modes of the modern Finnish local festivals and also the symbolic expressions typical to each of them are outlined. Then, the ritual meaning of these festivals is evaluated through a ‘thick description’ oftwo festival events. The goal is to make a holistic analysis of two local festivals utilizing (as well as testing) different anthropological (Clifford Geertz, Victor Turner) and sociological (Jurgen Habermas, Pierre Bourdieu) theories.